1981
DOI: 10.1021/bi00516a021
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cholesterol exchange between phospholipid vesicles

Abstract: The kinetics of cholesterol exchange between two populations of small unilamellar vesicles has been investigated. There is no change in the initial rate of this exchange process over a 100-fold change in the acceptor vesicle concentration at a constant donor concentration. These results are not consistent with a collision-dependent exchange mechanism. In support of transfer via the aqueous phase, the inclusion of a negatively charged lipid into the vesicles did not affect the exchange rate. Evidence for a wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(57 citation statements)
references
References 37 publications
5
50
1
1
Order By: Relevance
“…It has been demonstrated clearly that specific lipoprotein receptors on cell surfaces may facilitate and regulate the formation of collisional complexes (Goldstein and Brown, 1977). On the other hand, there is increasing evidence that receptor-independent transfer of lipids may, in part, involve the diffusion of lipid into the aqueous phase (Charlton et al, 1976;Charlton et al, 1978;Kao et al, 1977;Backer and Dawidowicz, 1978). In the present experiments, cholesterol in concentrations up to 10 M appeared to be stable in the aqueous phase, suggesting that saturation was reached at approximately that concentration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated clearly that specific lipoprotein receptors on cell surfaces may facilitate and regulate the formation of collisional complexes (Goldstein and Brown, 1977). On the other hand, there is increasing evidence that receptor-independent transfer of lipids may, in part, involve the diffusion of lipid into the aqueous phase (Charlton et al, 1976;Charlton et al, 1978;Kao et al, 1977;Backer and Dawidowicz, 1978). In the present experiments, cholesterol in concentrations up to 10 M appeared to be stable in the aqueous phase, suggesting that saturation was reached at approximately that concentration.…”
Section: Discussionmentioning
confidence: 99%
“…14 Perhaps most dramatic was the observation that cholesterol could transfer between two vesicle populations separated by a membrane impermeable to the vesicles. 15 The latter transfer was very slow. Transfer can be enhanced significantly by collision of donor and acceptor membranes.…”
Section: Cholesterol Movement Between Membranesmentioning
confidence: 98%
“…In disordered bilayers, cholesterol rapidly moves from one bilayer leaflet to the other (flip-flop) 188 , fully exploiting the orientational and translational freedom afforded in both leaflets. The flip-flop rate has been observed experimentally, giving a half-life of approximately 1 minute in a given leaflet 97,189 . Recent MD simulations showed rapid cholesterol flip-flop in membranes that mimic the composition of biological membranes, and confirmed that the flip-flop rate is much higher in the Ld phase than in the Lo phase 156,190 .…”
Section: Cholesterol Flip-flopmentioning
confidence: 99%